Nitrogen and Potassium Fertilization in a Guava Orchard Evaluated for Five Cycles: Effects on the Plant and on Production - Montes, Rafael Marangoni [UNESP]; Parent, Leon Etienne; Amorim, Daniel Angelucci de; Rozane, Danilo Eduardo [UNESP]; Parent, Sergie-Etienne; Natale, William; Modesto, Viviane Cristina [UNESP] (Soc Brasileira De Ciencia Do Solo, 2016)
Guava response to fertilization can be monitored through plant tissue analysis. Correct interpretation of these results, based on standard levels, is of great importance for correct nutrient management of the crop. However, standard levels are constantly criticized for not considering interactions among elements. To improve the nutritional diagnosis of 'Paluma' guava (Psidium guajava L., Myrtaceae), an experiment was conducted using nitrogen fertilization (0, 0.5, 1.0, and 2.0 kg per plant per cycle of N, with urea as a source with 45 % N), and potassium fertilization (0, 0.55, 1.1, and 2.2 kg per plant per cycle of K2O, with potassium chloride as a source with 60 % K2O) in an irrigated commercial area for five consecutive cycles, 2009 through 2012, observing the influence of fertilizers and climate and assessing yield and leaf element content, using the concept of isometric log ratios (ilr) to interpret leaf analysis results (N, P, Ca, Mg, K, and S). This paper showed that nutrient balances and nutrient concentration values can be interpreted coherently using compositional data analysis. Ranges of nutrient balances also were established for Paluma guava and validated through ranges grounded in nutrient contents currently used in Brazil. Nitrogen fertilization increased Paluma guava yield. The 0.5 kg N application rate per plant and the other studied treatments practically showed the same results, and their values were affected by pruning time as well as the nutrient balances.
Keywords: isometric log ratio (ilr); mineral nutrition; nutrient balance; compositional analysis